Correction: Titanium aminophosphates: synthesis, characterization and orange G dye degradation studies. Issue 114 (1st December 2016) - Rajini, Anumula; Nookaraju, Muralasetti; Chirra, Suman; Adepu, Ajay Kumar; Venkatathri, Narayanan
Abstract : Correction for 'Titanium aminophosphates: synthesis, characterization and orange G dye degradation studies' by Anumula Rajini et al., RSC Adv., 2015, 5, 106509–106518.